Alginate-derived solid acid catalyst for esterification of low-cost palm fatty acid distillate - Cheryl-Low, Y.L.; Theam, K.L.; Lee, H.V. (Elsevier, 2015)
Aluminum alginate (Al-A), a bio-based solid acid catalyst derived from natural brown algae extracted algin (polysaccharide) was studied for its physicochemical properties and catalytic activity as an acid catalyst via esterification of palm fatty acid distillate (PFAD). Based on the results, the presence of Al phases in the alginate system has successfully lowered crystallinity with winkled surface of bead form structure, which created large Lewis acid sites for the esterification process. Besides, the optimization study (RSM-CCD) showed that the methanol:PFAD ratio rendered the most significant effect on the PFAD conversion, followed by catalyst amount. The highest PFAD conversion of 92% was achieved at reaction conditions of 10 wt.% of catalyst concentration, 20:1 of methanol:PFAD molar ratio and reaction time of 230 min. High recovery of biodiesel was obtained for 2 consecutive cycles with PFAD conversion >80% under the optimized reaction conditions in the reusability test. The synthesized PFAD-derived biodiesel has complied with international biodiesel standards EN14214 and ASTM D6751. (C) 2015 Elsevier Ltd. All rights reserved.